PERAN PENGADILAN NEGERI INDONESIA DALAM PENYELESAIAN SENGKETA TRANSAKSI ELEKTRONIK INTERNASIONAL - Isdiyana Kusuma Ayu (Legality : Jurnal Ilmiah Hukum, 2018)
Electronic transactions or E-commerce are buying and selling transactions carried out through the internet. As a result of over the internet, the nature of e-commerce can be done without knowing the borders. When a default or fraud occurs in e-commerce conducted by one of the parties who are abroad, it must pay attention to the principle of International Private Law related to the Court forum, Arbitration, or other dispute resolution institutions. That means that it is necessary to pay attention to the basic arrangements for dispute resolution of international business transactions that have been regulated in Indonesia and the authority of the Indonesian District Court in resolving international electronic transaction disputes. In the juridical perspective as the basis for solving electronic transaction cases to be legal strengthening takes a sense of justice so that it can be seen that the basis of international e-commerce arrangements in accordance with Article 18 Paragraph (4) of the ITE Law. District Courts has a role to be the main and complementary institution in dispute resolution international electronic transactions.